Algebraic thinking ability of VIIth grade students in mathematics using SAVI learning model - Silviani, Siti Aminah; Mashuri, Mashuri; Wijayanti, Kristina (Unnes Journal of Mathematics Education, 2020)
Algebraic Thinking has become a research trend to be developed in secondary and elementary schools. Algebraic Thinking, according to Kieran (2004), includes generational ability, transformational ability, and global meta ability. Permendikbud No. 58 of 2014 indirectly states mathematics is being taught to hone the algebraic thinking ability. The SAVI learning model (Somatic, Auditory, Visual, Intellectual) combines physical movement, five senses, intellectual activity. The purpose of this study was to analyze the classical mastery of algebraic thinking ability of VIIth grade students, one of junior high school in Ungaran in the SAVI learning model, to analyze the algebraic thinking ability of VIIth grade students in the SAVI learning model and PBL (Problem Based Learning), to describe the algebraic thinking ability of VIIth Grade students in the SAVI learning model. The results showed that (1) Algebraic thinking ability of VIIth Grade students in SAVI learning did not achieve classical mastery; (2) The algebraic thinking ability in SAVI learning was better than in PBL; (3) Algebraic thinking ability of VIIth in SAVI learning showed that generational ability reached 47.84%; transformational ability reached 51%, and global meta ability reached 33.8%.